2004
DOI: 10.1002/mrc.1541
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Na+ binding parameters by relaxation analysis of selected 23Na NMR coherences: RNA, BSA and SDS

Abstract: Nuclear magnetic resonance provides several unique means of investigating the interactions between different inorganic ions and various macromolecules.23 Na is a quadrupolar nucleus, meaning that relaxation analysis of the various coherences allows the measurement of its binding to biological macromolecules. In this study, we analyzed the quadrupolar relaxation of 23 Na + longitudinal magnetization and single-and triple-quantum coherences in aqueous systems containing RNA, bovine serum albumin and sodium dodec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…For the 0.6 mM concentration of RRM2, the R 2 rates for 23 Na and 35 Cl increase by 12% and 60%, respectively. Such a strong protein effect on the relaxation of ions nuclei was observed earlier [26,27,30,48]. It could be seen that in the buffer R 1 = R 2 for both ions but at higher protein concentrations, the difference between R 1 and R 2 increases.…”
Section: Concentration Dependences Of R 1 and R 2 For 1 H 2 H 23 Nasupporting
confidence: 72%
See 1 more Smart Citation
“…For the 0.6 mM concentration of RRM2, the R 2 rates for 23 Na and 35 Cl increase by 12% and 60%, respectively. Such a strong protein effect on the relaxation of ions nuclei was observed earlier [26,27,30,48]. It could be seen that in the buffer R 1 = R 2 for both ions but at higher protein concentrations, the difference between R 1 and R 2 increases.…”
Section: Concentration Dependences Of R 1 and R 2 For 1 H 2 H 23 Nasupporting
confidence: 72%
“…This promising observation may be used to detect the aggregation of proteins. Torres et al have shown the applicability of this model for RNA, (1) 1∕T 1 = P free ∕T 1,free + P bound ∕ T 1,bound + bound , BSA, and sodium dodecyl sulfate (SDS) micelles that justify it as universal for biomolecules [27]. Similar studies were performed using 14 N, 35 Cl, and 37 Cl nuclei [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 89%
“…The studies were carried out at 3 and 7 T fields to obtain 1 H and 23 Na MR images, respectively. 23 Na MRI was performed using the 23 Na/ 1 H transceiver RF head coil and two pulse schemes -single-quantum (SQ) and triple-quantum filtering (TQF) [31][32][33][34][35][36][37][38][39][40][41][42][43][44]. To collect data in the case of SQ 23 Na MRI, the 3D GRE pulse sequence [45]…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…These methods yield estimates of the relaxation rate constants, the fraction of bound ions, the binding constants, the rotational correlation time (τ c ), and the quadrupolar coupling constant of the nucleus in its bound state. For example, Torres et al have determined the apparent binding constants (K f ) for Na + and a protein, bovine serum albumin (BSA), a nucleic acid yeast RNA, and a self-associating macroassembly, the detergent sodium dodecyl sulfate (SDS) using the relaxation behavior of selected 23 Na + magnetization coherences [34]. These three macromolecular systems were chosen as representatives of different classes of biomolecules that are likely to have diverse Na + -binding environments.…”
Section: Sodiummentioning
confidence: 99%